An Observational Study on the Management of Katigata Vata with special reference to Lumbar Spondylosis by Ashwagandhadi Kshirbasti (AYUSHDHARA, 2025)
Low back pain is the most prevalent clinical presentation in musculoskeletal disorder. Wrong postural habits and several stressful factors like incident back trauma, BMI, vehicular driving, daily spine loading contribute to the development of spinal disorders. Lumbar spondylosis is a common musculoskeletal disorder that is characterized by degenerative changes in the vertebral discs and the surrounding structures, leading to various clinical manifestations and impacts an individual's overall quality of life. Katigata vata is mentioned under Vatavyadhi with symptoms such as Katishula (lumbar pain), Aakunchan Prasaranyoh Shula (pain on flexion and extension), Graha (low back stiffness), as well as Pidanasahatva (tenderness). In Ayurveda, management of Katigraha is done on the basis of Chikitsa Siddhanta. Hence, this observational study aimed to assess the effect of Ashwagandhadi Kshirbasti (medicated herbal therapeutic enema) in Katigata Vata with special reference to lumbar spondylosis. This was an observational study, in which the data of thirty-four diagnosed cases of Katigata Vata were observed from the inpatient department of our institute. Ashwagandhadi Kshirbasti was administered in Kala Basti Krama along with Kati Basti. Wilcoxon Signed Rank Test was used for statistical analysis of the data. Statistically highly significant results (P< 0.0001) were found in all the clinical features of Katigata Vata. Assessment parameter like Roland-Morris Low Back Pain and Disability Questionnaire (RDQ) and WOMAC also shows highly significant reduction (P